Germline configuration of nfkb2, c-rel and bcl3 in childhood acute lymphoblastic leukemia (ALL) - Liptay, Susanne; Seriu, Taku; Bartram, Claus R.; Schmid, R. M. (Leukemia, 1997)
The well-known family of NF-κ B/Rel transcription factors is a central regulator of growth, differentiation and apoptosis in hematopoietic cell lineages. There is increasing evidence for their role in malignant transformation, especially in lymphomas. To study the possible involvement of NF-κB/Rel genes in the development of pediatric acute lymphoblastic leukemia (ALL), DNA samples from 140 patients were examined by Southern blot analysis. All samples revealed germline configuration of nfkb2, c-rel, and bcl3, indicating that structural alterations of these members of the NF-κ B/Rel family are extremely rare, if existing at all in childhood ALL.